Inversión económica y gestión patrimonial particular entre los prebendados de la España moderna: Córdoba (1500-1800) - Díaz Rodríguez, Antonio J. (2013)
It is tried through this paper to present a somewhat neglected aspect by both social history and economic history, the income analysis of local ecclesiastical elites, a significant financial element in the family, urban and regional environment. It starts from the case of the andalusian city of Cordoba as object of study in the context of Early Modern Spain.